Single customs territory implementation ; its effect on revenue collection and trade facilitation : case of Kenya - Bifwoli, Thomas W. (Strathmore University, 2016)
In June 2013, the presidents of Kenya, Uganda, and Rwanda decided to fast track the full implementation of East African Community’s Customs Union by launching a Single Customs Territory which is a form of a Customs Union. Its implementation and envisaged benefits have been documented. This study explores the details of aspects of SCT that could be having an effect on Kenya customs objectives which among others are revenue collection and trade facilitation. Data was obtained from Kenya Revenue Authority and analyzed. This data was for goods on transit from Mombasa through to Malaba exit point and of import data through Malaba. The period of the data under consideration was from January 2013 to December 2015. The defining date for this study is July 1 2014, when Single Customs Territory came in force. Analysis of the data was conducted to determine the effect of Single Customs Territory on trade facilitation and revenue collection before and after implementation of Single Customs Territory. Correlation analysis and a paired t-test ware done to compare extend of variance between the two periods, before and after SCT. The analysis showed that there has been significant increase in trade volumes of transit goods from Mombasa port through Malaba exit point. Similarly there has been an increase of goods imported through Malaba border point to Kenya. The increase in trade volumes is indicative of better trade facilitation by Kenya Revenue Authority after implementation of Single Customs Territory. Secondly the analysis showed that customs value reduced for both transit, and import goods through Malaba. Customs value is the basis for taxation. This means that with low customs value (tax base), revenue collection has also reduced. Based on this study, it is recommended that a review of the Single Customs Territory regime be undertaken by Kenya. The relevant government department should consider having an in-depth look into the observed negative effects of SCT in this case effect on revenue collection. Secondly necessary steps for implementation of a Customs Union needs to be completed including harmonizing of internal tariffs, common collection point of revenue among others. This will make it possible for the achievement of the SCT objectives.
This Dissertation is presented in partial fulfillment of the Degree of Public Policy and Management (MPPM)
Keywords: Trade; Single Customs Territory; Revenue Collection; Kenya; Tanzania; Uganda